Heroes on Stage: Robert Emmet, Charles Parnell, and Michael Collins in Three Irish Plays from Interwar Avant-garde to the 1990s - Kao, Wei H. (FOCUS: Papers in English Literary and Cultural Studies, 2022)
Once they enter the zone of public memory, historical figures, however celebrated they might be, are no longer able to speak for themselves, but become objectified by historians, creative writers, and interested parties down through the generations. Their portraits of revolutionaries might potentially counteract the subjugation imposed by colonial and anti-colonial powers and give them a more humane touch that prompts the audiences’ independent judgments. Representations of these historical figures might therefore put their contributions, personalities and even charisma under the microscope, challenging the historiography that tends to apotheosize them as heroes. The plays under discussion, chosen for their particularly avant-garde innovations and not yet fully discussed in the literature, are Dennis Johnston’s The Old Lady Says “No!” (1929), Larry Kirwan’s Mister Parnell (1992), and Tom MacIntyre’s Good Evening, Mr Collins (1995). These plays feature Robert Emmet, Charles Parnell, and Michael Collins, renowned yet still controversial Irish revolutionaries, respectively.